3D Printing Conductive Composites with Poly(ionic liquid) as a Noncovalent Intermedia to Fabricate Carbon Circuits. Issue 12 (23rd September 2021) - Lv, Xiaojie; Wang, Jingjing; Ding, Danning; Liang, Jiaojiao; Zhao, Zhongzheng; Liang, Yuan; Zhang, Zhenfei; Ye, Chunlin; Chen, Yuwei; Wei, Peng; Wang, Yanping; He, Yong; et al.
Abstract: In this study, a kind of imidazole type poly(ionic liquid) ([PEP‐MIM]Cl) is synthesized, which can disperse carbon effectively. [PEP‐MIM]Cl is used as an intermediate to coat carbon on the poly(acrylic acid)(PAA ‐co‐ MBA) via ion exchange to obtain conductive polymer composite (CPC). A series of characterizations are performed. Experiments show that carbon can be coated on the PAA ‐co‐ MBA uniformly, and compared with using carbon as filler, this method requires less carbon to achieve good conductive performance. The carbon layer on the polymer's surface is enriched via the swelling‐shrinking properties of PAA ‐co‐ MBA according to the SEM images. Furthermore, in combination with 3D printing technology, PAA ‐co‐ MBA can be designed into different shapes to achieve various functions such as pressure‐sensing element. Finally, a new type of CPC named carbon clad polymeric laminate (CCPL) is prepared by using the carbon coating method and 3D printing technology. It has the potential to replace copper clad laminate (CCL) and printed circuit board (PCB), to a certain extent. This technology expands the preparation method and application of the CPC such as flexible and wearable conductive fabrics. Abstract : In this study, a new methodology for coating carbon on the surface of polymers is designed to form conductive polymer composites. In addition, in combination with 3D printing technology and fabric, flexible and wearable conductive fabric composites can be prepared via this method, which expands the application of carbon composites.